PENGARUH STRATEGI PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN MENULIS PARAGRAF ARGUMENTASI SISWA KELAS X SMA ADABIAH 2 PADANG - Hidayati, Yulli; Basri, Irfani; Emidar, Emidar (Universitas Negeri Padang, 2016)
ABSTRACTÂ This is article of research is to description the effects of the using the inquiry learning strategy towards the skills of writing a paragraph argument of the ten grade students at SMA Adabiah 2 Padang. The type of this research is quantitative research done using experimental design. Based on the results of data analysis it was concluded the following three points. First, the skills of writing a paragraph argument of students of class X SMA Adabiah 2 Padang without using inquiry learning strategy is located on qualifications is more than enough (68,95). Second, the skills of writing a paragraph argument of students of class X SMA Adabiah 2 Padang using inquiry learning strategy is located on qualifications is good (80,95). Third, based on the result of uji-t, there is effects of inquiry learning strategy towards the skills of writing a paragraph argument of students of class X SMA Adabiah 2 Padang because taritmatic> t table (4,48> 167).Â Kata kunci: pengaruh, strategi pembelajaran inkuiri, dan paragraf argumentasi